2022
DOI: 10.1590/1980-220x-reeusp-2022-0147en
|View full text |Cite
|
Sign up to set email alerts
|

The association and intervention effect between eHealth literacy and lifestyle behaviors among Chinese university students

Abstract: Objective: Our aim was to evaluate the association between eHealth literacy and lifestyle behaviors to intervene among Chinese university students. Method: The Chinese eHealth Literacy Scale (C-eHEALS) questionnaire was used to investigate the eHealth literacy level and association with lifestyle behaviors among Chinese university students. Independent sample t-test and Pearson’s correlation coefficient were used by statistical software SPSS v20. Results: In the first round, 5,151 university students partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…According to the evidence, there is a positive association between health education of college students and lifestyle behaviors. 24 A better understanding of eating habits and overweight/obesity in college students supports the development of programs to promote healthy lifestyles in this population. 7 , 11 , 25 In this regard, Aljefree et al recommend that in order to reduce obesity among students, universities should guarantee access to healthy snacks and provide health education programs that promote healthy eating habits and lifestyles.…”
Section: Discussionmentioning
confidence: 99%
“…According to the evidence, there is a positive association between health education of college students and lifestyle behaviors. 24 A better understanding of eating habits and overweight/obesity in college students supports the development of programs to promote healthy lifestyles in this population. 7 , 11 , 25 In this regard, Aljefree et al recommend that in order to reduce obesity among students, universities should guarantee access to healthy snacks and provide health education programs that promote healthy eating habits and lifestyles.…”
Section: Discussionmentioning
confidence: 99%
“…During the COVID-19 pandemic, eHealth literacy may be an important factor in raising awareness of pandemic infectious diseases and forming healthy living habits among Korean middle school students ( 7 ) . Chinese college students had low eHealth literacy, and women were lower than men ( 8 ) . Under the condition of similar educational levels, Taiwan female college students had lower functional eHealth literacy than men ( 9 ) .…”
Section: Introductionmentioning
confidence: 99%
“…10 In 2017, Schnettler 5 conducted a survey on 372 college students in southern Chile, and found that 67.7% of them had food neophobia. Food neophobia is also related to living environments, computer skills, time spent visiting other countries, numbers of visits to ethnic minorities per week, lifestyle behaviors, 11 and the degree of exposure to university students with different cultures. 12 At present, the relationship between food neophobia and electronic health literacy is unclear.…”
Section: Introductionmentioning
confidence: 99%